PREPARING NEW TEACHERS THROUGH TEACHER-STUDY GROUP FOR PROFESSIONAL DEVELOPMENT - Sudirman Sudirman (Aksara: Jurnal Bahasa dan Sastra, 2017)
This article tries to present theoretical view and related reasarches to contemporary development of teachers professionalism. Dinamically consistent development of professional teachers should be continously maintained and enhanced following the unique character of teachers as social being. The reality has shown that there have been many gradutes from teachers-education institutions who have newly been teaching and those have not tauhgt at all. If they want to keep their knowledge and skill of teaching after graduation from S1 teahers-education they should have professional bridgingpre-professional phase through teacher-study group. What teacher-study group is is reviewed through reachable literatures.Key words: teacher/s, professionalism development, teacher-study group.Aziz, E.A. Profesionalisme Guru di Persimpangan Jalan. Harian Pikiran Rakyat 17 November 2011.Baratlett,S. 2006. An Evaluatiion of the Work of a Group of Best Practice Teacher Researchers. In Journal of In-Service Education.vol 28(3).p.527-540.16Dubetz, N. 2005. Improving ESL Instruction in aBillingual Program Through Collaborative, Inquiry-Based Professionalis Development. In D.J. Tedick (ed), Second Languange Teacher Education; International Prespectives. New Jersey, Lawrence Erlbaum Associates,Publishers.p.231-256.Edelfelt, R and Coble, C. 2004. University-School teacher education Partnerships in North Carolina. In Journal of In-aervice Education Vool 30 (3) .443-462.Gersten, R.et.al.2010. Teacher Study Group: Impact of the Professional Development Model on Reading Instruction and Student Outcomes in First Grade Classrooms. In American Educational Research Journal. Vol 47 (3) p.694-739.Grossman, P Thompson, C. 2004. District Policy and Beginning Teachers: A Lens on Teacher Learning. In Educational Evaluation and Policy Analysis Winter 2004, Vol.26, No. 4,pp.281-301Harrison, J.K. 2002. The Induction of Newly Qualified Teachers in Secondary Schools. In Journal of In-Service Education. Vol 28 (2) p.255-276. 20Johston, B. Pawan, F. and Taylor, R.M. The Professional Development of Working ESL/EFL Teachers: A pilot Study. In D.J. Tedick (ed), Second Language Teacher Education; International Perspectives. New Jersey, Lawrence Erlbaum Associates,Publishers.p.53.72.Jones, M. 2002. Qualified to Become Good Teachers: a case study of ten newly qualified teachers during their year of indication. In Journal of In-Service Education vol. 28 (3) p.509-526.Kearns, H. 2001. Competence-based Early Professional Development: First Impressions of the Northern Ireland Programme, in Journal of In-Service Education, 27:1, 65-82McLaughin, C and Black-Hawkins, K. 2004. A Schools-University Research Partnership: Understanding, Models, and Complexities. In Journal In-Service Education vol 30 (2) p.265-284Richards, J.C Farrell, T.S.C. 2005. Professional Development for Language Teachers; Strategies for Teacher Learning. Cambridge University Press. CambridgeScribner, J.P, Sawyer, K, Watson, S.T, and Myers, V.L. 2007. Teacher Teams and Distributed Leadership: A Study of Group Discourse and Collaboration. In Educational Administration Quarterly vol 43 (1) p.67-100Smith, L.C. 2005. The Impact of Action Reserach on Teaacher Collaboration an Professional Growth. In D.J. Tedick (ed), Second Language Teacher Education; International Perspectives. New Jersey, Lawrence Erlbaum Associates, Publishers.p.199-214.Spencer,P. 2011. Surviving your Teacher Practice. Open university Press. Berkshire.Stotsky, Sandra. 2006. Who Should Be Accountable for What Beginning Teachers Need to Know? In Journal of Teacher Education, Vol. 57, No. 3, May/June 2006 p.256-268Varghese, M and Wilberschied, L. 2002. Recosidering the Novice/Expert Dichotomy in the K-12 Mentor-Mentee Relationship. In Journal of In-Service Education, vol.28 (1) p.23-34.Williams, E Johnson, M. 2006. Politics and Principals: Beginning Black Teachers perceptions of Relationships with Administrators in 21st-Century Schools. In Improving School vol.9 Number 3 p.187-199